Lactic Acid-Producing Probiotic Saccharomyces cerevisiae Attenuates Ulcerative Colitis via Suppressing Macrophage Pyroptosis and Modulating Gut Microbiota - Sun, Siyuan; Xu, Xiuxiu; Liang, Ling; Wang, Xiaoli; Bai, Xue; Zhu, Lanping; He, Qijin; Liang, Huixi; Xin, Xin; Wang, Li; Lou, Chenxi; Cao, Xiaocang; et al. (Frontiers in Immunology, 2021)
Lactic acid, a metabolic by-product of host and intestinal microbiota, has been recovered as an active signal molecule in the immune system. In this study, a lactic acid biosynthesis pathway that directly produces lactic acid from glucose rather than ethanol with high production was reconstructed in Saccharomyces cerevisiae. The engineered S. cerevisiae showed anti-inflammatory activity in dextran sulfate sodium (DSS)-induced mice with improved histological damage, increased mucosal barrier, and decreased intestinal immune response. Lactic acid regulated the macrophage polarization state and inhibited the expression of pro-inflammatory cytokines in vivo and in vitro. Increasing the macrophage monocarboxylic acid transporter-mediated active lactic acid uptake suppressed the excessive activation of the NLRP3 inflammasome and the downstream caspase-1 pathway in macrophages. Moreover, lactic acid promoted histone H3K9 acetylation and histone H3K18 lactylation. Meanwhile, the engineered S. cerevisiae altered the diversity and composition of the intestinal microbiota and changed the abundance of metabolic products in mice with colitis. In conclusion, this study shows that the application of engineered S. cerevisiae attenuated DSS-induced colitis in mice via suppressing macrophage pyroptosis and modulating the intestinal microbiota, which is an effective and safe treatment strategy for ulcerative colitis.